(untitled) (Journal of Small Business Strategy (archive only), 2000)
The traditional case methodology has been used effectively in business education since 1921. Although this method of instruction promotes critical thinking, problem solving and communication skills, there are inherent disadvantages associated with it. In an attempt to address these disadvantages, the researchers utilized the living case methodology in a capstone senior strategy course. In the living case environment, students became active participants in the case. They interact with the decision makers of the company to gather the data, analyze it and determine the relevancy of the data in the decision making process. The concluding comments of the business owner as well as those of the instructor add insight to the advantages of the living case methodology as an instructional tool.